PERLINDUNGAN HUKUM KONSUMEN DALAM TRANSAKSI JUAL BELI MELALUI MEDIA SOSIAL INSTAGRAM MENURUT UU NO 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (Studi Kasus Reza Vs @Grosir_Olshop799) - Melya Stephani; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2020)
The purpose of this study is to determine the legal protection of consumers in online buying and selling transactions via social media Instagram associated with the sale and purchase of a sofa bed between Reza and @ grosir_olshop799 and to find out what legal remedies consumers can take if the seller is buying and selling online via social media. Instagram defaults on. The type of research used by researchers in this study is the normative juridical research method using the Statute Approach and the Conceptual Approach. Types and data collection techniques used are secondary and tertiary legal materials. The data analysis technique used in this study is a qualitative legal material analysis technique or method. The results showed that: (1) The legal protection of consumers in online buying and selling transactions through social media Instagram is associated with the sale and purchase of a sofa bed between Reza and @ grosir_olshop799 contained in UUPK No.8 of 1999; and (2) Legal remedies that can be taken by consumers if the seller in an online buying and selling transaction through Instagram social media defaults in the case of Kang Reza with @ grosir_olshop799 where there is a criminal case of fraud and threats so that the injured consumer can report to the police until he can enter the investigation stage.